Veteran Patient Experience Academy: Putting Veterans First. (27th July 2021) - Poorani, Ali A.; Kane, Vincent
With a national priority to make the Veteran Health Administration (VA) a leading customer service organization and provide patient-centric services to veterans and their families, the Wilmington VA Medical Center (W VAMC) partnered with the University of Delaware's Department of Hospitality and Sport Business Management at the Lerner College of Business & Economics to develop the VA Patient Experience Academy. The program focused on employee training and provided tools to enhance the veterans' experience, operationalized the VA Way (VA Core Values, Service Behaviors, Service Recovery), and Own the Moment. Phase 1 of the VA Patient Experience Academy launched with 25 managers in February 2019 and were followed by 5 cohorts including physicians, nurse practitioners, registered nurses, licensed practical nurses, medical staff assistants, and staff. The participants were selected from the W VAMC and 5 Community-Based Outpatient Clinics. The results were measured on 3 levels: Learning outcomes, application of training to practice, and the veterans' satisfaction scores. Scores in all 3 areas showed significant improvements.